Evaluasi User Experience (UX) pada aplikasi OVO dengan metode System Usability Scale (SUS) - Munandar, Hikam Rizqillah (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
OVO, an e-wallet company, introduced the OVO application as part of its digital strategy to cater to customer needs and stay competitive in the digital era. This study aims to assess the User Experience (UX) of the OVO application using the System Usability Scale (SUS) method. The research focuses on understanding user perceptions regarding functionality, intuitiveness, visual design, performance, support, and security aspects of the OVO application. The research methodology employed the System Usability Scale (SUS) questionnaire, which consists of structured questions to gauge user satisfaction and usability. The study participants were active users of the OVO application